50.5k views
3 votes
Solve the linear equation by using substitution.
x = 6-4y
2x-3y= 1

User Sreekar
by
5.0k points

1 Answer

0 votes

Answer:

The solution is x = 2 and y = 1.

Explanation:

The given equations are x = 6-4y and 2x-3y= 1.

We need to solve these equations by using substitution method.

Putting x = 6-4y in the other equation we get, 2(6 - 4y) - 3y = 1 or, 12 - 11y = 1 or, y = 1.

Now, putting the value of y in the other equation, we get x = 6 - 4 = 2.

User Angus Williams
by
4.8k points